Impact of diabetes on mental and functional well-being of older adults in Kerala - A. Anjana; P. Bindu (Journal of Geriatric Mental Health)
Objectives: Kerala is known to be India’s diabetes capital, with diabetes prevalence more than double the national average. Due to its high prevalence, imposed costs on health systems, and various adverse effects on patients, this disease is receiving more attention today. The purpose of the study is to find out the prevalence of self-reported diabetes and its impact on the mental health and physical health of older adults in Kerala. Methods: Data for the present study were taken from the Longitudinal Ageing Study in India (LASI), 2017–2018. The LASI is a nationally representative survey of 72,250 older adults aged 45 and above across all states and union territories of India. The study sample consists of 2497 older adults from Kerala. Descriptive statistics and bivariate and multivariate techniques were used to analyze the data. Results: The self-reported prevalence of diabetes in Kerala (27%) is found to be highest compared to other states. Diabetes is found to be more common among males than females. Among the respondents with diabetes, the likelihood of depression is higher among females (27%), probably due to their depressogenic cognitive style and low perceived control over life experiences. Functional well-being was more affected among females than males. Conclusions: The findings show that diabetes has a significant effect on the mental and functional well-being of older adults. The symptom profile indicates that the mental and functional competence of females with diabetes is impacted more than males which highlight the importance of addressing gender considerations both in early life and in later stages of life for women.